THE INFLUENCE OF USING THE SECIL APPLICATION IN INDONESIAN LANGUAGE LESSONS ON THE BEGINNING READING ABILITY OF CLASS II ELEMENTARY SCHOOL STUDENTSFIRST - Masitoh, Siti; Wibowo, Eko Wahyu; Mastoah, Imas (PIONIR: JURNAL PENDIDIKAN, 2025)
This research is motivated by the low initial reading ability of students and the lack of interesting learning media. This study aims to determine the effect of using the Secil application on the initial reading ability of second-grade students of Madrasah Ibtidaiyah Al-Jauharotunnaqiyyah Priuk. This study uses a quantitative method with a one-group pretest-posttest design in a pre-experimental approach. The subjects of the study were all 30 second-grade students with a saturated sampling technique. Data collection techniques were carried out through oral tests in the form of pretests and posttests. Data analysis was carried out through prerequisite tests in the form of Kolmogorov-Smirnov normality tests, hypothesis tests using paired sample t-tests, and Normalized Gain (N-Gain) calculations to determine the level of effectiveness of using the Secil application. The results showed a significant increase in initial reading ability after using the Secil application, with a significance value of the paired sample t-test of 0.000 <0.05, so Ho was rejected and Ha was accepted. In addition, the average N-Gain value of 0.7253 was included in the high category. These results indicate that the Secil application has a positive and effective influence as a learning medium in improving the initial reading skills of lower grade students of Madrasah Ibtidaiyah. Keywords: Reading Beginnings, Secil  Applications, Instructional Media